Interpersonal Communication, Lecturer Competence, and Job Satisfaction as Determinants of Organizational Commitment in Universities - Nora Silvia; Siraj Siraj; Munawar Munawar (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
The sustainability and quality of university institutions are significantly affected by the organizational commitment of their lecturers. Universities in developing nations frequently have enduring obstacles, including insufficient lecturer dedication, limited opportunities for professional development, and substandard working conditions. This study investigates the impact of interpersonal communication, lecturer proficiency, and job satisfaction on organizational commitment among educators in higher education institutions in Kota Langsa, Indonesia. A quantitative study approach was utilized, involving 120 lecturers from Universitas Sains Cut Nyak Dhien, selected via proportional sampling. Data were gathered through structured questionnaires and evaluated utilizing multiple regression analysis, t-tests, and F-tests. The findings demonstrate that interpersonal communication and lecturer proficiency substantially affect job satisfaction. Furthermore, interpersonal communication, competence, and job satisfaction each have a positive and significant effect on organizational commitment. These variables collectively contribute to a significant amount of variance in lecturers' commitment levels. The results highlight that lecturers' organizational commitment is influenced by personal characteristics and institutional dynamics, especially communication practices, competence development, and job satisfaction perceptions. University leaders are advised to improve interpersonal communication systems, invest in structured competency development programs, and establish equitable welfare policies that increase lecturers’ dedication and promote institutional sustainability.